IN SILICO MOLECULAR DOCKING STUDIES ON THE PHYTOCONSTITUENTS OF CADABA FRUTICOSA (L.) DRUCE FOR ITS FERTILITY ACTIVITY - AMUDHA, MURUGESAN; RANI, SHANMUGAM (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To study the effectiveness of phytocomponents from Cadaba fruticosa (L.) Druce against CYP 17 using computational molecular docking studies. The characterization of polycystic ovarian syndrome is hyperinsulinemia, menstural irregularities, long-term metabolic disturbances, and hyperandrogenism. Adrenal and ovarian androgen synthesis are induced by an enzyme, CYP 17 (P450c 17α). Due to increase in the activity of this enzyme, hyperandrogenism mainly occurs. By inhibiting the enzymatic activity, excess androgen synthesis can be prevented in ovarian theca cells. Literature study has reported that the gas chromatography mass spectrometry analysis on the ethanolic extract of the aerial parts of C. fruticosa possesses 20 compounds. Methods: Molecular docking analysis was performed for the reported 20 compounds against CYP 17 using Schrodinger Glide software. These results were compared with the docked score of fertility inducing drug clomiphene citrate. Results: All 20 compounds have exhibited moderate to potent inhibition with a range of −3.3 to −7.9. Androstan-3-one, 17-hydroxy-2, 4-dimethyl and 3-Trifluoroacetoxypentadecane have showed potent inhibition with the docking score of −7.9 and −6.8, respectively. Conclusion: The results revealed out that the compounds present in C. fruticosa can reduce the activity of CYP 17. This study throws a light on establishing the novel drug for infertility through experimental procedures. Keywords: Cadaba fruticosa, Glide-score, Infertility, In silico, CYP 17, Polycystic ovarian syndrome.